2016
DOI: 10.1007/s12020-016-1096-1
|View full text |Cite|
|
Sign up to set email alerts
|

CD28/CTLA-4/ICOS haplotypes confers susceptibility to Graves’ disease and modulates clinical phenotype of disease

Abstract: Graves’ disease, an autoimmune disease with heterogeneous symptoms including Graves’ orbitopathy, has a combined genetic/environmental background, where variations within CD28/CTLA-4/ICOS genes are considered as disease markers.Association of CD28c.17+3T>C(rs3116496), CTLA-4g.319C>T(rs5742909), CTLA-4c.49A>G(rs231775), CTLA-4g.*642AT(8_33), CT60(rs3087243), Jo31(rs11571302), ICOSc.1554+4GT(8_15) polymorphisms with susceptibility to Graves’ disease and clinical outcome was investigated. The study group comprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 46 publications
1
14
0
1
Order By: Relevance
“…Nevertheless, no uniform locus showed evidence for association with both GD and HT Uyghur patients, this may be due to genetic heterogeneity [39]. Consistent with previous studies, the polymorphisms of CD28 gene were considered as good candidates for GD patients [40], and the polymorphisms of STAT3 gene were good for HT [41]. Previously, the polymorphisms of IL2RA (CD25) gene was investigated in GD [42,43] and whether it is related to the aetiological variant of HT need more identification.…”
Section: Discussionmentioning
confidence: 67%
“…Nevertheless, no uniform locus showed evidence for association with both GD and HT Uyghur patients, this may be due to genetic heterogeneity [39]. Consistent with previous studies, the polymorphisms of CD28 gene were considered as good candidates for GD patients [40], and the polymorphisms of STAT3 gene were good for HT [41]. Previously, the polymorphisms of IL2RA (CD25) gene was investigated in GD [42,43] and whether it is related to the aetiological variant of HT need more identification.…”
Section: Discussionmentioning
confidence: 67%
“…Moderate forms occur in 5–10% of GD patients and severe forms in 1% of patients (1). Although autoimmune mechanisms are clearly involved, given the role of thyrotropin receptor antibodies and several cytokines, its precise pathogenesis remains poorly understood (1, 4, 5) The onset and progression of GO seem to be influenced by several factors such as smoking, thyroid dysfunction, a strong genetic influence (6, 7), and choice of treatment modality (2). Active GO disease involves some degree of motility dysfunction, diplopia, and sight-threatening conditions such as dysthyroid optic neuropathy and serious corneal exposure, resulting in corneal ulceration, or scarring (2, 4).…”
Section: Introductionmentioning
confidence: 99%
“…The principal characteristics and genotype distributions of the identified studies are shown in Table 3 . For SNP rs3087243 polymorphism, ten studies came from East Asian [ 12 – 21 ] and three studies from European population [ 22 24 ]. For the rs231775 polymorphism, there were 14 studies originated from East Asian [ 13 , 17 – 21 , 25 32 ], while the rest 8 studies were from European population [ 6 , 23 24 , 33 37 ].…”
Section: Resultsmentioning
confidence: 99%